Macroeconomic Variables and Financial Distress - Dah-Kwei Liou; MalcolmMalcolm Smith Malcolm Smith (Journal of Accounting, Business and Management (JABM), 2007)
A number of authors have suggested that macroeconomic factors impact significantly on the incidence of financial distress, and subsequently on corporate failure. However, macroeconomic factors rarely, if ever, appear as variables in predictive models seeking to identify distress and failure; the modellers generally suggest that the impact of macroeconomic factors has already been accounted for by financial ratio variables. This paper reports on a systematic study of this area, by examining the relationship between corporate failure and macroeconomic factors for UK manufacturing industry, to identify the most significant variables and to evaluate their usefulness in a predictive context. The outcomes of the study suggest that several macroeconomic variables are closely associated with failure, and have predictive value in specifying the relationship between financial distress and eventual failure.